Catalytic Tandem Reaction for the Production of Jet and Diesel Fuel Range Alkanes. Issue 6 (6th April 2018) - Li, Hu; Gui, Zhenyou; Yang, Song; Qi, Zhiwen; Saravanamurugan, Shunmugavel; Riisager, Anders
Abstract: Jet and diesel fuels are typically composed of C9 ‐C14 and C12 ‐C20 hydrocarbons, respectively, but the carbon‐chain length of sugar‐derived aldehydes and furanic compounds is no longer than C6 . Here, a cascade catalytic process involving alkylation and hydrodeoxygenation (HDO) of 2‐methylfuran (2‐MF) with different aldehydes is conducted to directly produce long‐chain alkanes with exclusive carbon number of C11 ‐C17 in overall yields of 50–84 %. Preliminary investigations on the alkylation of 2‐MF and formalin show that the relative density of Lewis and Brønsted acidic sites of zeolitic materials remarkably affect their catalytic activity and selectivity. Sn‐beta(12.5) with pronounced Lewis acidity (including the acid density and strength) exhibits higher catalytic performance in the alkylation than other zeolites, producing long‐chain oxygenates in 58–92 % yields. Even in aqueous solution, the Sn‐beta(12.5) catalyst can be reused for at least six reaction cycles with almost constant reactivity. More importantly, the co‐addition of Hf(OTf)4 with Pd/C greatly promotes C−O bond cleavage of the furan‐ring during the HDO process under mild reaction conditions, producing long‐chain alkanes in high yields of 84–94 %. Abstract : Biomass‐derived short‐chain molecules can be exclusively converted to C11 ‐C17 alkanes in high overall yields up to 84 % via cascade alkylation and HDO of 2‐methylfurfural (2‐MF) with different aldehydes. Lewis acidic Sn‐beta(12.5) zeolite is shown to be active and highly recyclable for the alkylation step (58–92 % yield), while Hf(OTf)4 together with Pd/C promote C−O bond cleavage of furanics during the HDO step under mild reaction conditions to produce jet and diesel fuel range alkanes (84–94 % yields).